DEVELOPMENTAL GUIDANCE AND COUNSELING IN A FAMILY SETTING (An Islamic Psychological Approach) Anwar Sutoyo - Sutoyo, Anwar (International Journal of Education, 2011)
This article puts forward an idea of implementation of developmental guidance andcounseling principles with Islamic perspectives in raising children in a family. Someconcepts of Islam closely related to the implementation of developmental guidance andcounseling in a family cover concepts of human nature, purpose of human creation,potencies of human, human characteristics, disaster happened to human, and death ofhuman. As for implementation of developmental guidance and counseling for children,it should start from the smallest unit of society, that is, family. The role of family inhelping a child to develop his/her potentials is very important because a child is bornto and brought up by parents. A child learns to develop in his/her environment. He/shealso learns how to interact with the environment properly from his/her parents. Althoughthe role of a family is very significant, not every family is able to play the role well.This is probably because of the mistakes in choosing spouses, feeding the family, andeducating the child. This could probably because of a role model crisis and lack of parentobservation. Considering the weaknesses, a preventive idea in the form of developmentalguidance and counseling is suggested. This idea can be applied by a family to help developthe biological, psychological, social, and faith potentials of a child. Therefore, the childcan grow and develop optimally in line with their age level and in accordance to the willof his/her Creator.Key words: developmental guidance and counseling, Islamic guidance and counseling,human potentials